A Nuanced Outlook of Human Perfection in Andrew Niccol's Movie, Gattaca - Ranjitkar, Palistha (Khwopa Journal, 2024)
Andrew Niccol's 1997 movie Gattaca pictures a world where parents can engineer genetically strong kids and those who come without prior engineering are seriously at disadvantage. While freedom of perfection creates a borderless autonomy for any parent to choose their child's destiny, equally it tames those who were not engineered by science but by fate. The movie therefore poses an important question regarding the definition of perfection in a society where genetics shapes much of an individual’s identity. This research employs Rene Descartes’ concept of mind-body dichotomy to justify the stance of Vincent’s eventual success to get into Gattaca despite being an invalid in a society where genetically engineered children are the highlight. It doesn’t however deal not so much with the age long debate about technology versus human as it does about subtle humane virtues, will power, desirability and ambitions that stands out despite the border of genetic engineering that tries to subdue it.